Meditation for tourists in Thailand: Commodifying a universal and national symbol - Brooke Schedneck (2018)
© 2014 Taylor and Francis. Meditation in Thailands international meditation centers is presented in advertisements as both a universal practice and a cultural icon that links Thailand to its ancient past. National religions and religious symbols serve to re-inscribe particular images, places, and practices as part of the national heritage. The practice of meditation is contextualized within Thailand and Thai culture, while it is also de-contextualized as a universal practice in which international meditators can participate. At the national level, meditation is a marker of Thailands difference and exoticism. At the same time as Thailands otherness is highlighted, meditation is also connected with universal systems of science and rationality. I argue that these selective elements serve to reinforce consumer values and constitute a commodification of meditation for tourists. I demonstrate that this does not detract from the practice for foreign communities, but that it is an example of the creative adaptations for reaching a wide variety of audiences. By looking at meditation guidebooks and promotional materials about meditation, this article contributes to scholarly dialogues of the commodification of religious practices.